2023
DOI: 10.3389/fpsyt.2022.1002625
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity, inhibition, and internet addiction in medical students of North of Iran

Abstract: BackgroundInternet addiction, a serious psychological disorder, has rapidly increased among students and caused substantial interpersonal impairments. On the other hand, some evidence has indicated that impulsivity is associated with addictive behaviors.ObjectivesThere are a few studies concerning the relationship between internet addiction and impulsivity in Iranian students. Therefore, this study aimed to evaluate the relationship between impulsivity and internet addiction in the medical students of Golestan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…While previous studies have often reported a higher prevalence of internet addiction among males, our study revealed a 1.9-fold higher risk in female medical students [11,20,25]. This finding aligns with the survey conducted by Haroon et al in Pakistan [26] and the study conducted in Qassim, Saudi Arabia [12].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While previous studies have often reported a higher prevalence of internet addiction among males, our study revealed a 1.9-fold higher risk in female medical students [11,20,25]. This finding aligns with the survey conducted by Haroon et al in Pakistan [26] and the study conducted in Qassim, Saudi Arabia [12].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, our prevalence rate was more significant than that among Iraqi medical students, where it was 71.8% with no severe addiction reported [ 18 ]. Additionally, our results exceeded those of a recent study conducted in North Iran, which found an addiction rate of 22.8% and a slightly higher severe addiction rate of 3.4%, which aligns more closely with our findings for severe addiction [ 11 ]. Furthermore, a study conducted by Chaudhari et al among medical students in India revealed a prevalence rate of 58.87%, with no students classified as severely addicted [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation